2016
DOI: 10.1080/21645515.2016.1219809
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of AS03-adjuvanted and non-adjuvanted trivalent inactivated influenza vaccines in elderly adults: A Phase 3, randomized trial and post-hoc correlate of protection analysis

Abstract: In this study we describe the immunogenicity results from a subset of older people (N = 5187) who participated in a Phase 3 randomized, observer-blinded trial of AS03-TIV versus TIV (Fluarix™) (ClinicalTrials.gov, NCT00753272). Participants received one dose of AS03-TIV or TIV in each study year and antibody titers against the vaccine strains were assessed using hemagglutination-inhibition (HI) assay at 21 d and 180 d post-vaccination in each vaccine group in the 2008/09 (Year 1) and 2009/10 (Year 2) influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…However, even though the primary endpoint was missed, clear benefits were observed in secondary and exploratory readouts. Specifically, efficacy against A/H3N2 influenza infection as well as all-cause mortality and pneumonia was demonstrated in a post hoc analysis 45 , 46 . Hence, although the Influence65 study did not support licensure, the study did highlight the potential benefits of an adjuvanted influenza vaccine for older adults, even during seasons with partially mismatched influenza strains.…”
Section: Introductionmentioning
confidence: 99%
“…However, even though the primary endpoint was missed, clear benefits were observed in secondary and exploratory readouts. Specifically, efficacy against A/H3N2 influenza infection as well as all-cause mortality and pneumonia was demonstrated in a post hoc analysis 45 , 46 . Hence, although the Influence65 study did not support licensure, the study did highlight the potential benefits of an adjuvanted influenza vaccine for older adults, even during seasons with partially mismatched influenza strains.…”
Section: Introductionmentioning
confidence: 99%
“…Three different bins were used to define the window for the second serum collection; 20% of samples were 3–4 months post-vaccination, 30% were 5–7 months post-vaccination, 40% were 8–10 months post-vaccination, and 10% were 11–12 months post-vaccination. The rationale for selecting more samples 5–10 months post-vaccination was based on publications indicating that protective HI titers were maintained up to 6 months before dropping to non-protective levels [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have indicated the benefits of vaccination can extend into the following season [ 5 , 10 , 11 , 12 , 13 , 14 ] while another study indicated that such antibody levels drop below accepted protective levels within a year [ 15 ]. Measurements of HI titers 180 days post-vaccination suggest that a significant portion of vaccinated subjects retain protective titers up to this point [ 16 ], but it is known that a reduction in vaccine effectiveness occurs later in the season, or in between seasons [ 17 , 18 , 19 , 20 ]. This has implications for those travelling between the northern and southern hemispheres, military personal posted to different regions of the globe, and at risk people vaccinated early during a season when influenza virus infections emerge late in the season.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is especially practical for important subgroups of the population, such as older adults living with frailty and/or chronic conditions, who are at an increased risk of influenza hospitalization [ 8 ] and severity of related outcomes [ 9 ], regardless of vaccination status [ 10 ]. That being said, few correlates have been validated in older adults, and those that have are based primarily on hemagglutination inhibition antibody responses [ 11 , 12 ], which do not provide appreciable cross-strain immunity within the subtypes of influenza. Immunological measures such as broadly neutralizing antibodies [ 13 ] and interferon gamma (IFNγ) producing T-cells [ 14 , 15 , 16 , 17 , 18 ] are cross-reactive within the subtypes of influenza A, which may provide protection in the years when there is a vaccine strain mismatch to circulating strain of influenza virus.…”
Section: Introductionmentioning
confidence: 99%